2017
DOI: 10.1111/cfs.12410
|View full text |Cite
|
Sign up to set email alerts
|

Children's trust in social workers: Scale development and relations to Children's engagement with social workers

Abstract: This research aimed to develop the children's trust in general social workers (CTGSW) scale. Psychometric properties, structural validity, construct, and concurrent validity of the scale were evaluated. Both linear and quadratic patterns between children's trust beliefs in social workers and their engagement with social workers were examined. A sample of 112 Italian vulnerable children (M = 11.4 years, SD = 1 month) were administered the Italian‐Children's Generalized Trust Beliefs scale, the CTGSW scale, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Responses ranged from 1 (totally impossible) to 5 (totally possible) with higher scores indicative of higher levels of interpersonal trust. Previous studies showed that this scale was suitable for children aged 9–12 years ( Rotenberg et al, 2015 ; Petrocchi et al, 2017 ). In this study, we reexamined the structure validity by a confirmatory factor analysis (CFA); the questionnaire exhibited an acceptable fit: χ 2 / df = 2.36, comparative fit index (CFI) = 0.92, Tucker–Lewis index (TLI) = 0.91, root mean square error of approximation (RMSEA) = 0.05, standardized root mean square residual (SRMR) = 0.04.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Responses ranged from 1 (totally impossible) to 5 (totally possible) with higher scores indicative of higher levels of interpersonal trust. Previous studies showed that this scale was suitable for children aged 9–12 years ( Rotenberg et al, 2015 ; Petrocchi et al, 2017 ). In this study, we reexamined the structure validity by a confirmatory factor analysis (CFA); the questionnaire exhibited an acceptable fit: χ 2 / df = 2.36, comparative fit index (CFI) = 0.92, Tucker–Lewis index (TLI) = 0.91, root mean square error of approximation (RMSEA) = 0.05, standardized root mean square residual (SRMR) = 0.04.…”
Section: Methodsmentioning
confidence: 99%
“…Each aspect contains four target groups, father , mother , teacher , and peer , and each target group includes two items. The CGTB Scale has been widely used in both international and Chinese studies, with acceptable reliability and validity (e.g., Xu et al, 2013 ; Rotenberg et al, 2015 ; Petrocchi et al, 2017 ). Gong and Luo (2016) adapted this scale to its Chinese version and proved its reliability and validity.…”
Section: Methodsmentioning
confidence: 99%
“…This is particularly relevant where children are called to build new relationships with peers, educators, and other adults. An example of the importance of the construction of interpersonal trust is highlighted in a study with children under protection services (Petrocchi et al, 2018). In these critical circumstances, not only does the success of the social interventions rely on building trusting relationships between the child's parents and the social workers, but also between the latter and the child in need of psychosocial adjustment (Hafford-Letchfield and Spatcher, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, when the paediatrician participation was obtained, on their side, parents easily agreed to be participants. It is highly likely that parental participation depends on the quality of their relationship with the paediatrician, as found by others [42,43]. This also means that a way to establish a continuous screening for children's mental health and speed up early diagnosis and intervention is increasing health professionals' awareness of that aspect.…”
Section: Limitationmentioning
confidence: 99%
“…This notwithstanding, the short version of the FYI may lead to a cost-effective and easy-to-administer instrument to be used by paediatricians during their pediatric surveillance on the general population. The early detection of atypical developmental trajectories may support medical decision-making on further steps for referral of the child to an early diagnostic assessment (which may enable early intervention when needed; [43][44][45][46][47][48].…”
Section: Conclusion and Implicationmentioning
confidence: 99%